+0  
 
+1
43
1
avatar

Solve s and t

s/4-2t=2

3t-6s=9

Guest Oct 22, 2017

Best Answer 

 #1
avatar+5227 
+1

s/4 - 2t  =  2     Add  2t  to both sides of this equation.

s/4  =  2 + 2t    Multiply through by  4 .

s  =  8 + 8t

 

3t - 6s  =  9     Since  s = 8 + 8t , we can substitute  8 + 8t  in for  s .

3t - 6(8 + 8t)  =  9        Distribute the  -6 .

3t - 48 - 48t  =  9        Add  48  to both sides.

3t - 48t  =  9 + 48       Combine like terms.

-45t  =  57        Divide both sides by  -45 .

t  =  -57/45       Reduce the numerator and denominator by  3 .

t  =  -19/15

 

To find  s , plug this value for  t  into one of the equations. I pick the equation  s = 8 + 8t .

 

s  =  8 + 8(-19/15)

s  =  8 -  152/15

s  =  -32/15

hectictar  Oct 22, 2017
Sort: 

1+0 Answers

 #1
avatar+5227 
+1
Best Answer

s/4 - 2t  =  2     Add  2t  to both sides of this equation.

s/4  =  2 + 2t    Multiply through by  4 .

s  =  8 + 8t

 

3t - 6s  =  9     Since  s = 8 + 8t , we can substitute  8 + 8t  in for  s .

3t - 6(8 + 8t)  =  9        Distribute the  -6 .

3t - 48 - 48t  =  9        Add  48  to both sides.

3t - 48t  =  9 + 48       Combine like terms.

-45t  =  57        Divide both sides by  -45 .

t  =  -57/45       Reduce the numerator and denominator by  3 .

t  =  -19/15

 

To find  s , plug this value for  t  into one of the equations. I pick the equation  s = 8 + 8t .

 

s  =  8 + 8(-19/15)

s  =  8 -  152/15

s  =  -32/15

hectictar  Oct 22, 2017

9 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details